PPREVALENCE OF COMPONENTS OF THE METABOLIC SYNDROME IN PATIENTS WITH ISCHEMIC HEART DISEASE IN YEREVAN POPULATION., ARMENIA - Mogadam, E. F.; Tadevosyan, A. E.; Podosyan, G. A.; Zelveian, P. H. (Evrazijskij kardiologičeskij žurnal (Online), 2013)
The research objective was aimed at the study of association of metabolic syndrome (MetS) and its components with coronary heart disease (CHD) among the population of Yerevan city (Armenia). Methods. During 2010-2011 in clinics of the Yerevan State Medical University and in the Center of preventive cardiology 320 patients with stable forms CHD (mean age 57.2±10.9 years) and 320 subjects without CHD (mean age 55.5± 11.7 years) were randomly selected. All patients have been surveyed according to current recommendations of clinical, instrumental and laboratory guidances. Diagnosis of MetS was defined by criteria AHA/NHLBI (2005). Biochemical analysis of blood made in hospital laboratories and anthropometrical indicators measured on standard procedures. Other data were obtained by use of the standard questionnaires. Study results were exposed to statistical processing by the parametric and nonparametric statistics methods, the zero hypothesis was rejected at p